Progressive Methods of the Harmfulness Evaluation of Transport in Terms of Emission Production - Dedík, Milan; Kendra, Martin; Senci, Matúš; Pribula, Daniel; Vojtek, Martin (My University, 2024)
Today, the key challenge is to ensure environmentally acceptable and sustainable transport. This paper analyzes the current state of emissions and greenhouse gases and their impact on the environment. In more detail, it is focused on relevant transport emissions data and their development in the Slovak Republic. It describes and analyzes proposals to improve the current state of rail transport and reduce greenhouse gas (GHG) emissions. Furthermore, it examines current transport trends and their impact on the environment and then analyzes and evaluates these relevant data concerning specific types of emissions. The differences between road, rail, and pipeline transport modes are analyzed and quantified through graphical analysis and analysis of variance (ANOVA) at 5% significance using IBM SPSS statistics software. A subsequent Scheffé post-hoc test is utilized. The usage of ANOVA enables the determination of whether the differences between the transport modes are statistically significant and generalizable or if they arise due to random variation. Based on the knowledge gained, specific measures and strategies are proposed that could contribute to a more efficient use of rail transport to reduce greenhouse gas emissions. The originality and novelty of the contribution lie in the connection between environmental science and applied statistics as well as in finding new progressive synergistic effects between them. The results provide important information for decision-making in the field of investment and planning of rail infrastructure and transport to promote environmental sustainability and reduce the negative environmental impact of rail transport. The research results contribute to the development of a sustainable transport system and will be used in other scientific research activities of the authors in more detailed research on individual proposed measures.
Pokrokové metody hodnocení škodlivosti dopravy z hlediska emisí
Keywords: emissions from transport; sustainable transport; greenhouse gas emissions; CO2 emissions; measures; emise dopravy, udrřitelná doprava, skleníkové emise, emise CO2, měření